Spin-Peierls transition in 2D Heisenberg model with bond phonons. - Lu, Wuyin. (2013)
Two kinds of possible dimerization patterns of Spin-Peierls transition in a 2D spin-1/2 Heisenberg model antiferromagnetic coupled to bond phonons with variable inter-chain coupling strength, corresponding to wave vectors Q=(π,0) andQ=(π,π), are investigated by using the Stochastic Series Expansion Quantum Monte Carlo method. The system is simulated by spin-1/2 Heisenberg Model with Nearest-Neighbor with inter-chain antiferromagnetic coupling. It is found that, at the same temperature, the (π, π) dimerization pattern is reached at a weaker inter-chain coupling than the (π, 0) dimerization pattern. At the same temperature and the same inter-chain coupling strength, when the system reaches the dimerization state, the energy of the (π, 0) pattern is lower, which means in this Model, the (π, 0) dimerization pattern is more stable.